THE HARDEST PROBLEMS IN NP - Fortnow, Lance (The Golden Ticket, 2013)
Tom Hull, chair of the University of Toronto Computer Science Department in 1970, wanted to hire Steve Cook. Steve Cook had just been denied tenure at the University of California at Berkeley. Cook enjoyed sailing, so Hull took him out on Lake Ontario to show that sailing near Toronto was just as good as sailing in San Francisco Bay. The ploy worked, and Steve Cook joined the University of Toronto faculty in the fall of 1970. A brilliant move, since Cook would soon become Canada’s most famous computer scientist. Cook studied the connections between logic and computer science. That fall